PERILAKU KONSUMTIF REMAJA PEREMPUAN TERHADAP TREND FASHION KOREA DI JAKARTA SELATAN - Poetri, Milla Riauzie; Ranteallo, Ikma Citra; Zuryani, Nazrina (JURNAL ILMIAH SOSIOLOGI (SOROT), 2015)
ABSTRACT In light of a growing interest in South Korea pop culture, widely known as hallyu or Korean wave, this study set out to identify its trend fashion through dramas, musics, online shop and mall. It also describe girls’ consumptive behaviors to buy cosmetics, clothes and other accesories. Descriptive approach with qualitative method were used to describe Karl Marx's commodity fetishism theory related to those behaviors. The findings of this study confirmed that girls in southern Jakarta bought Korean fashion products because its unique, simple, high-quality and made from natural ingredients cosmetics. Second, the beauty of idols had influenced them in consuming and willing to spend money on their appearance the Korean mode. They would satisfied if they can buy those branded stylish and products. Keywords: pop culture, Korean wave, fashion, consumptive behavior, girl, fetishism commodity